User Experience Analysis Of "Ayooklik.Com" Online Store Using Use Questionnaire In Determining Product Segmentation - Weking, Philipus Novenando Mamang; Sudarma, Made; Saputra, Komang Oka (Majalah Ilmiah Teknologi Elektro, 2020)
Over time, the market function of the convention has now developed into an updated market namely Online Store. Online Store Business is currently supported by a marketing strategy called Product Segmentation. In the implementation of the marketing strategy, sometimes it is not in a position to satisfy all their customers at any time because not all requirements of every customer can be fulfilled by the Online Store company. To answer this problem, a solution that can be offered to solve the problem is to carry out the usability analysis process of the Ayooklik.com online store system in determining Product Segmentation. The results showed that Ayooklik.com customers were satisfied because the Ayooklik.com system was easy to learn so product needs were even greater. The high and low usability of the Ayooklik.com system affects the price of a product sold.